Development of an Intertextual E-Module on Intermolecular Forces with Potential to Improve Students’ Concept Mastery and Critical Thinking Skills - Hany Ayudyaningrum; Wiji Wiji; Tuszie Widhiyanti (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an intertextual-based e-module on the concept of intermolecular forces that has the potential to improve students' conceptual mastery and critical thinking skills. The research was conducted using the ADDIE model, which concluding at the development stage. The e-module was designed by integrating multiple chemical representations (macroscopic, submicroscopic, and symbolic) to enable students to master the concept comprehensively. In addition, the e-module was developed based on critical thinking indicators. The results showed that the e-module had characteristics of being self-instructional, self-contained, stand-alone, adaptive, user-friendly, consistent, multimedia-integrated, intertextual-based, and attentive to learning principles. The developed e-module was tested for feasibility by media experts, language experts, subject matter experts, and instructional method experts. The feasibility test results indicated that the e-module was declared feasible with some suggestions for improvement. The suggestions and feedback from the experts were used to revise the product design. Thus, an intertextual-based e-module on the concept of intermolecular forces was obtained, which has the potential to improve students' concept mastery and critical thinking skills.